Analysis of Internal Control's Effect on Prevention Fraud in Kalimantan: Systematic Literature Review - Syarifah Yustin Ekasari; Chilvia Ardilla; Dinda Chaerunissa Hermawan; Leones Natasia (Jurnal Price : Ekonomi dan Akuntasi, 2024)
The impact of fraud on organizations cannot be overstated, as it can lead to severe financial losses, damage to reputation, and potential bankruptcy. This comprehensive study thoroughly explores the role of internal controls in mitigating fraud, specifically in the Kalimantan region. It delves into various factors such as duty separation, employee training, pressure, and control systems to understand their impact on fraud prevention. The findings of the study, based on an in-depth literature review, highlight the crucial role of robust internal controls in reducing the risk of fraud. Importantly, the research does not just stop at theoretical findings but also offers practical guidance for companies in Kalimantan, providing actionable strategies for enhancing fraud prevention through prioritizing internal control mechanisms and employee training. This real-world application of the research findings makes it highly valuable for companies looking to strengthen their fraud prevention strategies in Kalimantan.